Clearance of apoptotic cells and the control of inflammation - Savill, John (Henry Stewart Talks, 2009)
Historical perspective, Inflammation re-invented as innate immunity, Clearance by phagocytes defines the meaning of cell death, Suppression of inflammation, Apoptotic cell phagocytosis, Reprogramming, Regulation of immune responses, DCs ingest apoptotic cells, Apoptotic cells inhibit DC maturation, Apoptosis and regulatory T cells, Modulation of parasite infestation, Control of macrophage-directed cell death